Charge transport in pure and mixed phases in organic solar cells - Melianas, Armantas; Pranculis, Vytenis; Spoltore, Donato; Benduhn, Johannes; Inganäs, Olle; Gulbinas, Vidmantas; Vandewal, Koen; Kemerink, Martijn (Advanced energy materials, 2017)
In organic solar cells continuous donor and acceptor networks are considered necessary for charge extraction, whereas discontinuous neat phases and molecularly mixed donor-acceptor phases are generally regarded as detrimental. However, the impact of different levels of domain continuity, purity, and donor-acceptor mixing on charge transport remains only semiquantitatively described. Here, cosublimed donor-acceptor mixtures, where the distance between the donor sites is varied in a controlled manner from homogeneously diluted donor sites to a continuous donor network are studied. Using transient measurements, spanning from sub-picoseconds to microseconds photogenerated charge motion is measured in complete photovoltaic devices, to show that even highly diluted donor sites (5.7%-10% molar) in a buckminsterfullerene matrix enable hole transport. Hopping between isolated donor sites can occur by long-range hole tunneling through several buckminsterfullerene molecules, over distances of up to ≈4 nm. Hence, these results question the relevance of “pristine” phases and whether a continuous interpenetrating donor-acceptor network is the ideal morphology for charge transport.
Gesehen am 27.11.2019